Gender in livestock development: Marisa Mitchell - Mitchell, M. (International Livestock Research Institute, 2019)
Marisa Mitchell, AVID volunteer at ILRI Vietnam, shares her ‘aha’ moment when she really understood the central importance of women in livestock development. This film was produced to mark the International Women’s Day 2019 which is themed ‘Think equal, build smart, innovate for change’.